Group homes for people with intellectual disabilities : encouraging inclusion and participation - Clement, Tim (Jessica Kingsley Publishers, 2010)
Group homes are the dominant form of residential accommodation for people with severe learning or intellectual disabilities, and yet there are significant problems within these living environments. This book seeks to highlight the key issues for both residents and staff, and offers practical suggestions for improving community living. Based on original empirical research and drawing on extensive field notes, the book paints a picture of life in group homes today. The authors propose a framework for increasing community presence and participation, and consider the barriers to be overcome if pro.